Phytotherapy in periodontics - Vasques, Ana Maria Veiga [UNESP]; Matheus, Henrique Rinaldi [UNESP]; Gusman, David Jonathan Rodrigues [UNESP]; Cury, Marina Tolomei Sandoval [UNESP]; dos Reis-Prado, Alexandre Henrique; Quintino Trizzi, Juliana [UNESP]; Emerenciano Bueno, Carlos Roberto [UNESP] (My University, 2020)
Periodontal diseases continue to be the most commonly occurring oral diseases in modern times. Plaque-induced gingivitis and periodontitis are caused by the penetration of pathogens from the bacterial plaque into the connective tissue, resulting in an inflammatory condition. Gingivitis affects the connective tissue of the gingiva, while periodontitis affects the entire periodontal apparatus. Many adjuvant therapeutic modalities have been tested for the treatment of these conditions. Among them, herbal therapies have shown anti-inflammatory, antioxidant and antimicrobial properties. These phytotherapic are incorporated into mouth rinses, dentifrices, chewing gums, adhesives, and gels in order to prevent and even treat gingivitis. With respect to periodontitis, gels, chips and extracts containing herbs have provided many benefits when used as adjuvants to scaling and root planning. In addition, its benefits are also observed in wound healing following periodontal surgery. Hence, this chapter will present aspects of phytotherapy in periodontics.
Keywords: Gingivitis; Herbal medicine; Periodontics; Plant extracts